Protection of Nitrogenase in Azotobacter vinelandii - Shah, Vinod K. (1973)
The site or sites that protect nitrogenase from O(2) inactivation in vivo are sensitive to sodium azide or 2,4-dinitrophenol. Both components of nitrogenase can be synthesized when oxidative phosphorylation is disrupted.